2016
DOI: 10.21273/hortsci.51.3.268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Spectral Quality and Intensity of Light-emitting Diodes on Several Horticultural Crops

Abstract: Light-emitting diode (LED) lamps signify one of the most important advances in artificial lighting for horticulture over the last few decades. The objective of this study was to compare the cultivation of four horticultural plants using a conventional white LED tube (T0) light against one with a good spectral fit to the maximum photosynthetic response (T1) at two intensities. The experiment was carried out with two types of young lettuce, tomato, and bell pepper plants. In a controlled environment cham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 14 publications
4
29
0
Order By: Relevance
“…In the case of plants cultivated with high light intensity in T1, an average increase of 20% was seen compared with those cultivated under T0, in which the fresh weight of radish increased by 45%. A change in spectrum and intensity was shown previously to improve the parameters of vegetative growth by Yang and Park (2015); by Samuolien_ e et al (2011) in radish; by Urrestarazu et al (2016) in lettuce, to-mato, and pepper; and by Burattini et al (2017) in spinach. T1 produced a significant increase in fresh weight that varied between 12% for lettuce and 45% for radish.…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…In the case of plants cultivated with high light intensity in T1, an average increase of 20% was seen compared with those cultivated under T0, in which the fresh weight of radish increased by 45%. A change in spectrum and intensity was shown previously to improve the parameters of vegetative growth by Yang and Park (2015); by Samuolien_ e et al (2011) in radish; by Urrestarazu et al (2016) in lettuce, to-mato, and pepper; and by Burattini et al (2017) in spinach. T1 produced a significant increase in fresh weight that varied between 12% for lettuce and 45% for radish.…”
Section: Resultsmentioning
confidence: 77%
“…T1 produced a significant increase in fresh weight that varied between 12% for lettuce and 45% for radish. Working in similar conditions, Urrestarazu et al (2016) found that the vegetative growth doubles and, in some cases, can be greater than 200%, whereas Samuolien_ e et al (2011) achieved significant growth (90% more) in radish.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations